PENERAPAN ETIKA BISNIS ISLAM PADA WAROENG STEAK AND SHAKE MEDAN - Rizka Ar Rahmah (Universitas Islam Negeri Sumatera Utara, 2020)
This research aims to determine the concept of business ethics which is implemented in Waroeng Steak and Shake, SM Raja Medan Branch. Waroeng Steak and Shake is a culinary business that underlies every business activity according to the rules of the Al-Quran and Sunnah. This study used a qualitative approach with data validation techniques by extracting information from related respondents and by making direct observations for data verification. Research results can be known and felt by researchers about the existence of different religious nuances compared to the culinary business in general at Waroeng Steak has implemented Islamic business ethics properly using the concepts of Shiddiq, tabligh, amanah and fathanah, which guarantees good and halal ingredients and honesty in transactions, the delivery of da'wah through business, and honesty in financial reports. However, this shop needs to have an increase in service and spiritual intelligence. So it is suggested to make a program Smile, Greetings and Greetings in improving services and prayer activities in turn to improve spiritual intelligence.